RELASI KUASA SUAMI DAN DAMPAKNYA TERHADAP KEKERASAN DALAM RUMAH TANGGA (KDRT) DI DESA SUKARARA KECAMATAN SAKRA BARAT - Laila Ramdani; Jepri Utomo; Nursaptini Nursaptini (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the power relations between husbands and wives and the forms of domestic violence that occur in Sukarara Village, West Sakra District, East Lombok Regency. This research is motivated by the persistence of a patriarchal culture that places men as the dominant party in the household, thus creating an unbalanced power relationship and impacting violence against wives. The study used a qualitative approach with a case study method. Data collection techniques were carried out through observation, semi-structured interviews, and documentation. The research subjects consisted of 8 people and 3 informants. The results show that the power relations between husbands and wives in Sukarara Village are still dominated by owner-property, head-complement, and senior-junior partner relationships. In the owner-property pattern, the wife is positioned as the husband's property so that the husband feels he has full rights to control and regulate her. In the head-complement pattern, the husband is seen as the head of the family who has the main authority, while the wife is only a complement in the household. The senior-junior partner pattern shows a hierarchical relationship that places the husband in a superior position due to economic, age, and cultural factors. These power relations then lead to the emergence of various forms of domestic violence (DV), including physical violence, psychological violence, and sexual violence. Violence occurs due to the legitimacy of patriarchal culture, the subordination of women, gender inequality, and the normalization of male dominance within the house.